2016
DOI: 10.2135/cropsci2015.03.0154
|View full text |Cite
|
Sign up to set email alerts
|

Sweetpotato Responses to Mid‐ and Late‐Season Soil Moisture Deficits

Abstract: Soil moisture‐dependent, quantitative information on sweetpotato [Ipomoea batatas L. (Lam)] plant processes is vital for crop management and modeling because of the projected shrinking and uneven distributions of rainfall and irrigation water supply due to climate change. This study was conducted to quantify the growth, physiology, biomass, and storage root yield responses of sweetpotato under four evapotranspiration‐based irrigation treatments (100, 60, 40, and 20% ET) in sunlit growth chambers. Irrigation tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 62 publications
2
25
0
Order By: Relevance
“…The physiological changes caused by the ageing of foliar tissues contribute to a reduction in water loss rates during plant development, which has an intrinsic relationship with the transpiration of plants (Tardieu, ). In fact, lower transpiration values may be interesting for plants in drought conditions, as they prevent water loss and ensure a higher degree of hydration to plant tissues, and consequently greater water‐use efficiency (Gajanayake & Reddy, ). Plants with lower transpiration values for the same photosynthesis value are more efficient in water use and have greater tolerance to drought (Hepworth, Doheny‐Adams, Hunt, Cameron, & Gray, ).…”
Section: Discussionmentioning
confidence: 99%
“…The physiological changes caused by the ageing of foliar tissues contribute to a reduction in water loss rates during plant development, which has an intrinsic relationship with the transpiration of plants (Tardieu, ). In fact, lower transpiration values may be interesting for plants in drought conditions, as they prevent water loss and ensure a higher degree of hydration to plant tissues, and consequently greater water‐use efficiency (Gajanayake & Reddy, ). Plants with lower transpiration values for the same photosynthesis value are more efficient in water use and have greater tolerance to drought (Hepworth, Doheny‐Adams, Hunt, Cameron, & Gray, ).…”
Section: Discussionmentioning
confidence: 99%
“…Makbul et al (2011), reported a 28% decrease in chlorophyll content when the leaf water potential decreased from −0.88 to −1.18 MPa in soybean. Decreased chlorophyll content and increased carotenoids contents during drought stress have been reported in many species (Wang et al 2003;Gajanayake and Reddy 2016;Wijewardana et al 2016), depending on the severity and duration of the stress. Loss of chlorophyll content is considered as the main cause of reduced photosynthesis under drought stress.…”
Section: Introductionmentioning
confidence: 93%
“…photochemical damage to PS II under water-limited conditions. Decreased chlorophyll and increased carotenoid contents have been reported for many crop species under soil moisture stress (Massacci et al 2008;Guha et al 2010;Gajanayake and Reddy 2016). Carotenoids form a key part of the plant antioxidant defense system; however, they are susceptible to oxidative damage.…”
Section: Chlorophylls and Carotenoidsmentioning
confidence: 99%
“…Previous studies showed that, in general, soil moisture, soil and air temperature, nitrogen fertilizers are such environmental factors (Meyers 2014). More specifically, the early-season soil moisture, temperature, and nitrogen fertilizer determine root initiation; and the mid-and late-season ones determine biomass and yield (Villagarcia et al 1998, Ukom et al 2009, Gajanayake et al 2013Gajanayake and Reddy 2016).…”
Section: Introductionmentioning
confidence: 99%